Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 7980000 species occurrences available in GBIF matching the query: { "Country" : [ "is Japan" ] } The dataset includes 7980000 records from 2039 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0070867-200221144449610/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences